2016
DOI: 10.1038/srep32215
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate enhance recovery from wastewater by mechanism analysis and optimization of struvite settleability in fluidized bed reactor

Abstract: Since phosphorus, a non-renewable and non-substitutable resource, has become the principal contributor and limiting factor to water eutrophication, achieving phosphorus removal and recovery from wastewater is pretty essential. Even though struvite crystallization process has been widely used for phosphate (P) recovery in wastewater treatment, its application is hampered by difficulties controlling small particle size and crystal growth. This study was conducted to control the settleability of struvite by calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…According to thermodynamics, smaller struvite crystals are supposed to dissolve in favour of the growth of larger crystals with time (i.e. Ostwald ripening mechanism (Delgado-López et al 2014;Fang et al 2016)). Formation of struvite has been studied intensively in communal and industrial waste water.…”
Section: Introductionmentioning
confidence: 99%
“…According to thermodynamics, smaller struvite crystals are supposed to dissolve in favour of the growth of larger crystals with time (i.e. Ostwald ripening mechanism (Delgado-López et al 2014;Fang et al 2016)). Formation of struvite has been studied intensively in communal and industrial waste water.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the concentration of component-ions has direct correlations with the saturation index (SI) of the solution, hence directly influences the nucleation and growth. Higher initial concentrations of P, keeping all other component concentrations and operating conditions constant, resulted in larger diameter of struvite crystals (Fang et al, 2016). Fang et al (2016) observed an increase of > 300% in diameter of the struvite crystals (20.5 µm to 69.3 µm) when the initial concentration of P was increased from 155 mg.L -1 to 930 mg.L -1 .…”
Section: Influence Of Molar Ratiomentioning
confidence: 92%
“…Precipitation of struvite is subject to a number of physico-chemical parameters: pH (Nelson et al, 2003;Fang et al, 2016), component-ion molar ratios (Nelson et al, 2003;Wang et al, 2005), intensity of mixing (Fang et al, 2016), and presence of foreign ions (Muryanto & Bayuseno, 2014;Saidou et al, 2015).…”
Section: Influence Of a Number Of Process Parameters On Struvite Precmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, struvite is a potential source of phosphorus, nitrogen and magnesium and therefore it is a main compound recovered from wastewater and converted into useful fertilizer containing these elements (for example Refs. [19][20][21][22][23]). The recovery of struvite from wastewater is especially essential in view of phosphorus [15,24,25].…”
Section: Introductionmentioning
confidence: 99%